Empowering Health Cadres as a Toddler Posyandu Team to Improve the Knowledge and Skills of Cadres Through Counseling and Training - Novita Rina Antarsih; Debbi Yantina; Aticeh Aticeh (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
The COVID-19 pandemic has exacerbated nutritional problems for children under five and many Posyandu for toddlers are not operating, thus increasing delays in preventing stunting and stunting growth for toddlers. This health cadre empowerment activity is carried out because health cadres are a team in the toddler posyandu. This is done by increasing the knowledge and skills of cadres so that they can perform early detection of stunting and make referrals. This activity goes through 7 steps of serial activities, namely Preparing, Participatory Program, Asset Reinventing, Designing, Communicating, Implementing, Evaluating. Activity results: knowledge of cadres about stunting increased from a score of 70 to 90, understanding the interpretation of measurement results for toddlers so that cadres' skills in early detection of stunting increased Implication: the application of digital applications that make it easier for cadres to detect stunting early to prevent and refer.